2017
DOI: 10.3892/br.2017.871
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and antimigratory effects of Cratoxy formosum extract against HepG2 liver cancer cells

Abstract: Abstract. The aim of the present study was to investigate the molecular mechanisms underlying Cratoxylum formosum (CF) Dyer-induced cancer cell death and antimigratory effects in HepG2 liver cancer cells. The cytotoxic, antiproliferative and antimigratory effects of CF leaf extract on human liver cancer HepG2 cell lines were evaluated using sulforhodamine B, colony formation, and wound healing assays. In addition, apoptosis induction mechanisms were investigated via reactive oxygen species (ROS) formation, cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…The cytotoxicity of Cratoxy formosum extract against Hep G2 cells at 500 µg/mL, after 48 h of treatment is similar to those observed in this study (SSpe-treated Hep G2) at same concentration and time [29] Similar cytotoxicity was observed at 250 µg/mL in DSea-treated WiDr cells at 48 h.…”
Section: Resultssupporting
confidence: 84%
“…The cytotoxicity of Cratoxy formosum extract against Hep G2 cells at 500 µg/mL, after 48 h of treatment is similar to those observed in this study (SSpe-treated Hep G2) at same concentration and time [29] Similar cytotoxicity was observed at 250 µg/mL in DSea-treated WiDr cells at 48 h.…”
Section: Resultssupporting
confidence: 84%
“…Recent studies revealed that most of the marine plant derived anticancer drugs including fucoidan acted in dose-dependent decline of colony formation ability and cell migration in HepG2 cancer cells. In the present study was totally obsessed with similar result, regarding the effect of fucoidan on colony formation and cell migration assays as reported elsewhere [33,28,31]. This dietary brown seaweed was eventually proven and encompassed with active compounds against tumor cells [34].…”
Section: Discussionsupporting
confidence: 67%
“…In fact, dietary plants are encompassed in terms of medical values that can serve as invaluable source for anticancer drug development. Moreover, the anti-cancer drugs available in the dietary supplement are quite safe and effective regulation of normal cell metabolism and also accelerating the programmed cell death by interrupting the uncontrolled cell proliferation [28]. It is well-know that the brown seaweeds are being used as medicinal dietary supplements in most of the Asian countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SRB was used to determine cytotoxicity as previously described (Buranrat et al, 2017). After 24-h exposure, cells were fixed with 10% ice-cold trichloroacetic acid (TCA) and then incubated in darkness at 4°C for an hour.…”
Section: Methodsmentioning
confidence: 99%